Quality of Emergency Hospital Care for Children with Severe Mechanical Traumas in Pediatric and Non-Pediatric In-Patient Hospitals: Results of the Retrospective Cohort Study - Alexey V. Chernozubenko; Dmitry V. Prometnoy; Fedor G. Sharshov; Galina A. Prometnaya (Вопросы современной педиатрии)
Background: Comparability of the quality of medical care for children in different types of in-patient hospitals remains a subject of debate.Objective: Our aim was to compare the quality of emergency hospital care for children with severe traumas in pediatric and non-pediatric in-patient hospitals.Methods: Retrospective cohort (continuous) research. We analyzed medical records of intensive care patients (form 003/u) with severe traumas at the age of 1 month to 18 years hospitalized to in-patient hospitals of Rostov Oblast in 2010–2014. The quality of medical care was assessed according to duration of diagnostic maneuvers that led to the diagnosis and surgical activity (frequency of surgical interventions for the condition that led to hospitalization).Results: We analyzed the data on 134 children with severe mechanical traumas hospitalized to pediatric (n = 29) and non-pediatric (n = 105) in-patient hospitals. Lifethreatening traumas (Pediatric Trauma Score 8 points) were recorded in 26 (90%) and 79 (75%) children, respectively (p = 0.127). The duration of the diagnosis stage in two groups was 135 (120; 160) and 140 (110, 210) minutes, respectively (p = 0.548). Surgical activity was higher in pediatric in-patient hospitals: surgical interventions were performed in 16 (55%) children compared to 37 (35%) cases in the group of children admitted to non-pediatric hospitals (p = 0.052).Conclusion: The quality of emergency in-patient hospital care for children with severe traumas in pediatric and non-pediatric hospitals does not differ significantly.